Kebiasaan Tinggal Di Rumah Etnis Timor Sebagai Faktor Risiko Tuberkulosis Paru - Naben, Alice Ximenis; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background : Pulmonary Tuberculosis disease is a disease that can infect directly that is caused by Mycobacterium tuberculosis that can be transmitted from patients with Pulmonary Tuberculosis through spray of sputum mediated by the air. In the year 2010, the District of Northern Central Timor was ranked as the five for East Nusa Tenggara Province and had ethnic houses that if were viewed from healthy house requirements were very far from fulfilling the requirements. The purpose of this study is to view the habit of living in Timorese ethnic houses as a risk factor for tuberculosis. Methods : The type of study is observational with case control approach. There were 100 samples that consisted of 50 cases and 50 controls that were collected at random. Data from study results were then analysed in univariate and bivariate analyses using chi square statistic with conditional method. Results : of analyses on 8 variables, there were 6 variables that had significant associations i.e. the habit of living in Timorese ethnic house (OR= 3,8; 95%CI= 1,6 - 8,7), area of ventilation (OR= 6,2; 95%CI = 2,5 - 15,7), cross ventilationÂ (OR= 4,2; 95%CI =1,8 - 9,7), the type of wall of the house (OR= 4,7; 95%CI =1,9 - 11,4), the type of floor of the house (OR= 3,7; 95%CIÂ The results of multivariate analyses showed that there were 1 variables that were dominant in causing pulmonary tuberculosis i.e. crowdedness of home (OR= 9,2; 95%CI= 3,5 - 24,5). Conclusion : that there is a relationship between the habit of living in Timorese ethnic houses, area of ventilation, the presence of cross ventilation, the type of wall of the house, the type of floor of the house and the crowdedness of home with the occurrence of pulmonary tuberculosis. Â Keywords : Habit of living, pulmonary tuberculosis, physical environment of home, preventive practice.